2020
DOI: 10.1016/j.drugalcdep.2020.108260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of COVID-19: A cohort comparison study of drug use and risky sexual behavior among sexual minority men in the U.S.A.

Abstract: Highlights Marijuana and illegal drug use declined during the COVID-19 pandemic. Condomless anal sex with casual male partners declined during the COVID-19 pandemic. Associations between illegal drug use and sex outcomes were stronger during COVID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 42 publications
4
56
1
2
Order By: Relevance
“…Table 1 shows the characteristics of the included studies. These included studies were conducted in various high income countries (HICs) and low-middle income countries (LMICs) ( Figure 2 ): 23% of the studies were done in the United Kingdom [ 31 , 32 , 33 , 34 ], 6% in Brazil [ 35 ], 17% in the United States [ 36 , 37 , 38 ], 6% in Wales [ 39 ], 12% in Italy [ 40 , 41 ], 6% in Israel [ 42 ], 6% in the United States, Canada, United Kingdom, Australia, and other countries [ 43 ], 6% in Turkey [ 44 ], 6% in Belgium [ 45 ], 6% in Poland [ 46 ], and 6% in HICs and LMICs [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the characteristics of the included studies. These included studies were conducted in various high income countries (HICs) and low-middle income countries (LMICs) ( Figure 2 ): 23% of the studies were done in the United Kingdom [ 31 , 32 , 33 , 34 ], 6% in Brazil [ 35 ], 17% in the United States [ 36 , 37 , 38 ], 6% in Wales [ 39 ], 12% in Italy [ 40 , 41 ], 6% in Israel [ 42 ], 6% in the United States, Canada, United Kingdom, Australia, and other countries [ 43 ], 6% in Turkey [ 44 ], 6% in Belgium [ 45 ], 6% in Poland [ 46 ], and 6% in HICs and LMICs [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies showed evidence on the impact of COVID-19 and family planning services [ 36 , 40 , 44 ], six studies reported on COVID-19 impact on maternal and child services [ 31 , 33 , 34 , 44 , 45 , 47 ], and eleven studies reported on COVID-19 and sexual behavior [ 32 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, there is real concern that sexual distancing is not a durable response to the pandemic. Studies among MSM from early in 2020 demonstrated a reduction in sexual risk–taking behaviors [ 4 , 8 ]. Yet, “quarantine fatigue,” a relaxation of social distancing practices, likely carries over to sexual distancing.…”
mentioning
confidence: 99%
“…As those reporting fewer partners may still have sexual partners, we explored overall reductions in numbers of all types of sexual partners of 25% and 50% (equivalent to 50% and 100% reduction among 50% of MSM). As two other online surveys of US MSM found no change in numbers of casual sexual partners 18 or slight increases in total but no change in unprotected sexual partner numbers, 17 we also considered scenarios with no change in partner numbers. We modelled observed reductions in PrEP initiations, PrEP use and HIV testing among those on PrEP, based upon a study at a Boston PrEP clinic.…”
Section: Methodsmentioning
confidence: 99%
“…In late April, reduced HIV and STI testing were reported in Baltimore, with many health department staff focussing on the COVID-19 response. 11 MSM in the US – among whom 70% of new HIV infections occur nationally – reported fewer sexual partners because of COVID-19 in two national surveys 2,10 , but slightly increased or stable partner numbers in two other surveys, 17,18 all conducted in April-May 2020. In these surveys, MSM also reported reduced access to HIV testing, 2,17 care 2 and PrEP 2,17 due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%